Aerobic Anoxygenic Photosynthesis Is Commonly Present within the Genus Limnohabitans - Kasalický, Vojtěch; Zeng, Yonghui; Piwosz, Kasia; Šimek, Karel; Kratochvilová, Hana; Koblížek, Michal (Applied and environmental microbiology, 2018)
The genus Limnohabitans (Comamonadaceae, Betaproteobacteria) is a common and a highly active component of freshwater bacterioplanktonic communities. To date, the genus has been considered to contain only heterotrophic species. In this study, we detected the photosynthesis genes pufLM and bchY in 28 of 46 strains from three Limnohabitans lineages. The pufM sequences obtained are very closely related to environmental pufM sequences detected in various freshwater habitats, indicating the ubiquity and potential importance of photoheterotrophic Limnohabitans in nature. Additionally, we sequenced and analyzed the genomes of 5 potentially photoheterotrophic Limnohabitans strains, to gain further insights into their phototrophic capacity. The structure of the photosynthesis gene cluster turned out to be highly conserved within the genus Limnohabitans and also among all potentially photosynthetic Betaproteobacteria strains. The expression of photosynthetic complexes was detected in a culture of Limnohabitans planktonicus II-D5T using spectroscopic and pigment analyses. This was further verified by a novel combination of infrared microscopy and fluorescent in situ hybridization.IMPORTANCE The data presented document that the capacity to perform anoxygenic photosynthesis is common among the members of the genus Limnohabitans, indicating that they may have a novel role in freshwater habitats.
Keywords: Multigene Family; Limnohabitans; bchY; Bacterial Proteins; fotosyntéza; fylogeneze; Comamonadaceae; Photosynthesis; Phylogeny; photosynthetic bacteria; IR microscopy; freshwater Betaproteobacteria; FISH; Genes, Bacterial; Aerobiosis; pufM; bakteriální proteiny; bacteriochlorophyll; aerobióza; multigenová rodina; bakteriální geny